2013
DOI: 10.5414/cp201816
|View full text |Cite
|
Sign up to set email alerts
|

Safety and pharmacokinetics of PF-04360365 following a single-dose intravenous infusion in Japanese subjects with mild-to-moderate Alzheimer’s disease: a multicenter, randomized, double-blind, placebo-controlled, dose-escalation study

Abstract: PF-04360365 was safe and well tolerated in Japanese subjects. Pharmacokinetics and plasma pharmacodynamic responses in Japanese subjects were comparable to those in Western subjects. *No longer affiliated with Pfizer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 0 publications
0
20
0
Order By: Relevance
“…It diminishes the amyloid burden through an outflow of Aβ from the hippocampus induced by the reduction of the peptide in plasma 77 . Results of the clinical trials evidenced no significant improvement in cognitive impairment of patients with mild to moderate AD 78,79 and at the moment is being tested for the treatment of cerebral amyloid angiopathy (CAA) (https://clinicaltrials.gov; Identifier: NCT01821118).…”
Section: Drugmentioning
confidence: 99%
“…It diminishes the amyloid burden through an outflow of Aβ from the hippocampus induced by the reduction of the peptide in plasma 77 . Results of the clinical trials evidenced no significant improvement in cognitive impairment of patients with mild to moderate AD 78,79 and at the moment is being tested for the treatment of cerebral amyloid angiopathy (CAA) (https://clinicaltrials.gov; Identifier: NCT01821118).…”
Section: Drugmentioning
confidence: 99%
“…Ponezumab is a humanized IgG2 mAb that binds to the C-terminal region of Aβ (Aβ33-40). Although Phase 1 studies of ponezumab showed sufficient safety [64,65], its Phase 2 trials revealed no significant cognitive improvement in patients with mild to moderate AD [66]. The development of ponezumab for AD was discontinued, although it is still in Phase 2 trials for cerebral amyloid angiopathy (CAA).…”
Section: Immunotherapies Targeting Aβmentioning
confidence: 99%
“…113 And another clinical trial also showed similar results. 114 GSK-933776 is a humanized Fc-attenuated/inactivated anti-Ab monoclonal antibody. GSK933776 showed pharmacological activity and engaged target in plasma and CSF without causing brain amyloid-related imaging abnormalities-edema (ARIA-E/H) in patients with mild AD or MCI.…”
Section: Amyloid-targeted Therapiesmentioning
confidence: 99%